Synthesis of C4-alkynylisoxazoles via a Pd-catalyzed Sonogashira cross-coupling reaction. Issue 16 (18th March 2019) - Yang, Wen; Yao, Yongqi; Yang, Xin; Deng, Yingying; Lin, Qifu; Yang, Dingqiao
Abstract : A Pd-catalyzed Sonogashira cross-coupling reaction for the synthesis of C4-alkynylisoxazoles from 3, 5-disubsitituted-4-iodoisoxazoles and terminal alkynes was described, which could afford the corresponding products with high yield (up to 98%). Abstract : A Pd-catalyzed Sonogashira cross-coupling reaction for the synthesis of C4-alkynylisoxazoles from 3, 5-disubsitituted-4-iodoisoxazoles and terminal alkynes was described, which could afford the corresponding products with high yield (up to 98%). The results indicated that the steric effect from the group at the C3 position of the isoxazole had greater influence on the cross-coupling reaction than that from the group at the C5 position. In addition, the group at the C3 position of the isoxazole showed negligible electronic effects on the cross-coupling reaction. Furthermore, a gram-scale reaction of the Sonogashira coupling reaction was also investigated. Finally, a plausible mechanism for the Sonogashira coupling reaction was proposed.